Dynamic Energy Consumption using Current and Power Reading Detector with Appliance Indicator - Naim, Nur Haziah; Subramaniam, Tamil Selvan; Ab Rahman, Azmanirah; Zakaria, Normah (Research and Innovation in Technical and Vocational Education and Training, 2021)
Abstract: In Malaysia, the uses of excessive loads or electrical appliance on sockets is increasing because of user habit and behaviour. This has a negative impact on consumers where this can threaten the safety of consumers who use electrical appliances and cause damage to appliances. Therefore, Current and Power Reading Detectors with Appliance Indicators were developed to help users detect the reading of current and power on electrical appliance before use on a socket. The project developed is a tool that detects the current and power readings of an electrical appliance using the Blynk application via mobile phone as well as electrical appliance indicators. This project is intended as a safety measure to help users overcome the problem of excessive load consumption on sockets either in residential homes or buildings that use a voltage not exceeding 240V and a current not exceeding 20A. This device uses ACS712 current detector as detector while Node MCU is used as micro controller and Arduino IDE as system controller. The development of this detector will display current, voltage and power readings on the LCD display and on the Blynk application display. While the LED serves as an indicator for the output of the received power reading and the display of the equipment indicator. The development of this project uses the Engineering Design Process (EDP) design model as a guide to develop a project that includes eight key steps. In conclusion, this device is tested to detect current and power readings from electrical appliance well and has good safety features to help users use electrical appliance safely. Keywords: Current, Power, ACS712, Blynk.